Pressure Becomes Power: The Mediating Effect of Eustress on the Self-Efficacy to Performance - Azzahra, Fariha; Fitriyani, Nurul; Rahayu, Indah (Journal Economic Business Innovation, 2025)
Purpose: The present study examines the mediating role of eustress in the association between self-efficacy and employee performance to provide better input on involvement of psychological resources and positive stress to employee performance at work setting.Method: Census sampling, a quantitative method using SEM for data analysis via SmartPLS to assess direct and indirect relationships among variable.Findings: The results demonstrate that self-efficacy positively significantly influence employee performance and self-efficacy has a significant effect on eustress. In turn, eustress has a favorable effect on performance and mediates the link between self-efficacy and performance. Highly self-efficacious persons can rather convert job stress into active distress to elevate motivation, adjustment, and efficacy.Novelty: The aim of the paper is to introduce the concept of eustress to the self-efficacy performance stream of research and to provide empirical evidence that would suggest eustress mediates the link between self-efficacy and optimal performance, thus also serves as a psychological conduit that converts perceptions of human capability to actual performance.Implications: The results highlight the need for a supportive and demanding workplace and providing self-efficacy training. These departmental strategies would enhance sustained high performance of an organization and balance employee well-being.